Effects Of Explicit Knowledge And Metacognitive Thoughts On Iowa Gambling Task Performance - Ermiş, Ece Naz (My University, 2017)
Decision-making is an essential cognitive function in everyday life. The Iowa Gambling Task (IGT) is a popular neuropsychological task that assesses decision-making through reward and punishment in the context of learning from past experiences. Differences in decision-making performances of healthy participants predicted by metacognition levels and having explicit knowledge during IGT were examined. 76 female and 12 male students at Istanbul Kultur University completed the IGT and Metacognition Questionnaire-30 (MCQ-30). After completing task implementations, each participant was asked a list of questions relating to their strategy on IGT and categorized into two groups depending on their level of explicit knowledge. As in conventional analysis of IGT, each block's net score was calculated. Results indicated that group with knowledge had significantly higher net scores and consistently improved their performances across 5 blocks of IGT than group with no explicit knowledge. Study showed there is a difference between healthy controls' learning strategies and this difference reflected to their decision-making performances. In risky blocks of IGT as the task progresses, negative beliefs about uncontrollability and danger subscale scores of metacognition has a negative effect on advantageous decision making, whilst a higher score on cognitive confidence subscale predicts disadvantageous decision making. Results and suggestions for future studies were discussed in light of previous work.
Keywords: IOWA Kumar Testi; Karar verme; Üst biliş